Two new records of the Family Celaenopsidae (Acari: Mesostigmata) from China, with description of a new species - Xu, Yun; Li, Xiang; Zhang, Fei-Ping (Zootaxa, 2019)
Two species of the mite family Celaenopsidae, Pleuronectocelaeno barbara Athias-Henriot, 1959 and Schizocyrtillus fuzhouensis sp. nov., were recorded in China. Specimens were collected in bark and rotten wood on Pinus massoniana Lamb. in Sanming city and Fuzhou city, respectively. Information on current distribution, host association and morphological diagnostics of these two mites is provided.